Therapeutic Effects of VEGF Gene-Transfected BMSCs Transplantation on Thin Endometrium in the Rat Model. (30th October 2018) - Jing, Zhao; Yi, Yan; Xi, Huang; Sun, Lun-Quan; Yanping, Li
Abstract : Objective . Bone mesenchymal stem cells (BMSCs) transplantation has a therapeutic effect on the thin endometrium in animal researches and clinical trials. The present study aims at assessing whether transplantation of VEGF-transfected BMSCs (VEGF-BMSCs) have a better therapeutic effect on endometrial regeneration and endometrial receptivity compared with BMSCs therapy alone. Methods . Sprague-Dawley (SD) rats were used in the study. Thin endometrium model was established with 95% ethanol injection into uterine. VEGF-BMSCs or BMSCs was transplanted via tail vein IV injection. Endometrial thickness, morphology, and pinopodes were assessed by hematoxylin and eosin (HE) staining and scanning electron microscope (SEM). The proteins and mRNAs expressions of markers for endometrial cells and endometrial receptivity were measured after treatment. The fertility testing was done to assess the embryo implantation efficiency. Results . VEGF-BMSCs transplantation significantly increased endometrial thickness compared with the BMSCs group and the control group. There was no significant difference in endometrial thickness between VEGF-BMSCs group and sham operation group. Importantly, in protein level, expressions of cytokeratin, vitamin, VEGF, LIF, and integrin αν β 3 in VEGF-BMSC group were increased dramatically compared with those of the control group and BMSC group both 4 days and 8 days after stem cells transplantation. Accordingly, mRNA expression of LIF and integrin α ν β 3 was significantly upregulated compared with those of the control group and BMSC group both 4 and 8 days after treatment. The pinopodes were developed better in the VEGF-BMSCs group and the sham operation group compared with BMSCs group and the control group. The number of embryo implantation is largest in the sham operation group, followed by VEGF-BMSCs group, BMSCs group, and the control group. Conclusions . Transplantation of VEGF gene-transfected BMSCs may be a better therapeutic treatment for thin endometrium than stem cell therapy alone.